Factors Associated With The Prevention Of Symptoms Of Acute Respiratory Infections (Ispa) In Pt.X - Sugiarto, Sugiarto; Safitri, Fika Maria; Yenni, Melda (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Acute Respiratory Tract Infection (ARI) is an acute respiratory tract disease with a variety of symptoms. ARI is also a disease very closely related to environmental sanitation and clean living behaviour. Environmental conditions are wet, humid, hot and smelly at PT X. It is known that the hot conditions of the factory caused by the rubber processing process can have an impact on the onset of various diseases such as ARI symptoms. This research is a quantitative study with a Cross Sectional design. The purpose of this study was to determine the factors associated with the prevention behaviour of Acute Respiratory Infection (ARI) at PT X in 2023. The sample in this study were 55 workers. The sampling method used Total Sampling. The results showed that there was a significant relationship between knowledge with a p-value = 0.004, and motivation with a p-value = 0.000 with the behaviour of preventing Acute Respiratory Tract Infection (ARI) at PT X in 2023. It is recommended to provide counselling, supervision, sanctions to workers who do not use PPE and give rewards or awards to workers who always use PPE and conduct regular checks regarding ARI.